Gallium-68 in Medical Imaging - Martiniova, Lucia; Palatis, Louis De; Etchebehere, Elba; Ravizzini, Gregory (Current Radiopharmaceuticals, 2016)
Over the past several years, Positron Emission Tomography (PET) imaging agents labeled with 68Gallium (68Ga) have undergone a significant increase in clinical utilization. 68Ga is conveniently produced from a germanium-68/gallium-68 (68Ge/68Ga) generator. Because of the compact size and ease of use of the generator, 68Ga labeled compounds may be more cost-effective than PET radioisotopes that are cyclotron-produced. The convenient half-life of 68Ga (T1/2=68 min) provides sufficient radioactivity for various PET imaging applications, while delivering acceptable radiation doses to patients. This chapter summarizes the emerging clinical utilization of 68Ga-based radiotracers in medical imaging.
Keywords: somatostatin receptor scintigraphy